(untitled) (Journal of Comparative Social Work, 2014)
The essay presents a reflection on being a foreign and inexperienced social worker within a Norwegian social work context. I discuss challenges I have met in my work with when Asperger syndrome is diagnosed and reflect on power relations and the issue of self-determination within the field, in addition to analysing some critical incidents that made me rethink and reconstruct all of my experiences. I view my story from different angles and find different perspectives that show various ways of perceiving one thing. I discover the dangerousness of thinking in “black and white” and placing things in exclusive extremes, and lastly, I understand that I need to learn to solve problems by changing attitudes towards them.